Gender considerations in the promotion of climate-smart agriculture practices: Evidence from rural Tanzania - Pamuk, Haki; Muijlwijk, Miriam van; Wattel, Cor; Deering, Karl; Asseldonk, Marcel van (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This is the second of two Info Notes that summarize insights from five studies conducted between 2018 and 2021 on upscaling climate-smart agriculture (CSA) practices among small-scale farmers in rural Tanzania. The first Info Note - Upscaling climate-smart agriculture practices: working with Farmers’ Field and Business Schools and Village Savings and Loan Associations in rural Tanzania - summarizes key findings and policy recommendations on upscaling CSA practices. This second Info Note focuses on findings concerning the gender dynamics in promoting the adoption of CSA practices, and provides recommendations for policy makers and practitioners. The Note begins with the study background, main concepts, and methodology before presenting and discussing results and making recommendations.